A Multi Center, Epidemiological Study of Bone Tuberculosis in Southwest China from 2011 to 2023 - Xiaopeng Qin; Boli Qin; Chenxing Zhou; Chong Liu; Tianyou Chen; Jichong Zhu; Chengqian Huang; Shaofeng Wu; Rongqing He; Songze Wu; Sitan Feng; Jiarui Chen; et al. (Journal of Epidemiology and Global Health)
Abstract Background Despite continued efforts to manage and control Tuberculosis (TB) in China, it remains a major health concern. Bone tuberculosis (Bone-TB), a common form of extrapulmonary tuberculosis, still adds considerably to the global TB case load. Diagnosing Bone-TB is often difficult as its symptoms can be similar to other bone or joint diseases, which leads to delayed detection and treatment. Currently, comprehensive reports on the epidemiological aspects of Bone-TB in China are scarce. Methods This retrospective study analyzed demographic and clinical data from 2,191 patients diagnosed with Bone-TB in Southwest China between January 2011 and September 2023.This study fully reveals the characteristics of Bone-TB in Southwest China. Results The overall trend of bone tuberculosis was a slow rise. Among 2191 patients, males, farmers, aged 42–68 years, and people with HIV and diabetes are the priority groups for the prevention and treatment of Bone-TB. The majority of the infected spines (1556/2191) were located in the thoracic vertebra (759/2191) and lumbar vertebra (715/2191). Forty-nine (2.24%) patients had drug-resistant TB (DR-TB). Forty-five (2.05%) died during the treatment. The total and actual hospitalization. Costs amounted to $3,837.10 and $1,914.35 (p < 0.01). Patients with DR-TB incurred the highest costs, amounting to $4,968.37. Cervical TB, with a prevalence of 5 patients (6.10%), exhibited the highest rates of catastrophic expenditures. Conclusions From 2011 to 2023, the yearly occurrence of Bone-TB in southwestern China exhibited a rising pattern, marked by notable distinctions in terms of gender, age, and regional variations, indicating localized clustering characteristics.